Catalytic Kinetic Resolution and Desymmetrization of Amines - Liu, Wei; Wang, Donglei; Zhang, Dekun; Yang, Xiaoyu (Synlett, 2022)
Optically active amines represent critically important subunits in bioactive natural products and pharmaceuticals, as well as key scaffolds in chiral catalysts and ligands. Kinetic resolution of racemic amines and enantioselective desymmetrization of prochiral amines have proved to be efficient methods to access enantioenriched amines, especially when the racemic or prochiral amines were easy to prepare while the chiral ones are difficult to be accessed directly. In this Account, we systematically summarized the development of kinetic resolution and desymmetrization of amines through nonenzymatic asymmetric catalytic approaches in the last two decades.1 Introduction2 Kinetic Resolution of Amines2.1 Kinetic Resolution of Amines via Asymmetric Transformations of the Amino Group2.1.1 Asymmetric N-Acylations2.1.2 Asymmetric N-Alkylation2.1.3 Asymmetric N-Arylation2.1.4 Other Asymmetric N-Functionalizations2.1.5 Asymmetric Dehydrogenation of Amines2.1.6 Selective C–N Bond Cleavage of Amines2.2 Kinetic Resolution of Amines via Asymmetric Transformations without Amino Group Participating3 Enantioselective Desymmetrization of Amines3.1 Desymmetrization of Diamines3.2 Desymmetrization of Prochiral Monoamines4 Conclusion and Outlooks
Keywords: chiral amines; kinetic resolution; enantioselective desymmetrization; asymmetric catalysis